If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sin(10x) + -1cos(5x) = 0 Remove parenthesis around (10x) ins * 10x + -1cos(5x) = 0 Reorder the terms for easier multiplication: 10ins * x + -1cos(5x) = 0 Multiply ins * x 10insx + -1cos(5x) = 0 Remove parenthesis around (5x) 10insx + -1cos * 5x = 0 Reorder the terms for easier multiplication: 10insx + -1 * 5cos * x = 0 Multiply -1 * 5 10insx + -5cos * x = 0 Multiply cos * x 10insx + -5cosx = 0 Reorder the terms: -5cosx + 10insx = 0 Solving -5cosx + 10insx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10insx' to each side of the equation. -5cosx + 10insx + -10insx = 0 + -10insx Combine like terms: 10insx + -10insx = 0 -5cosx + 0 = 0 + -10insx -5cosx = 0 + -10insx Remove the zero: -5cosx = -10insx Divide each side by '-5osx'. c = 2ino-1 Simplifying c = 2ino-1
| 16x^(2/3)-4x^(1/3)-2=0 | | 49+5y=-2y | | y=4x+130 | | X^2+8x-960=0 | | -3/5y=15 | | f(x)=5x^2+20x-3 | | 3x+240=600 | | 0=4r | | X^2-12x-960=0 | | y=4x^1/2 | | 4(x-3)-5(2x+1)= | | logx+log(x-6)=2 | | 14(2+r)=84 | | 2a+2b+7a-8+6b= | | (4x)*2=32/2 | | y=(-3x^5)(ln(x)) | | (2x-4)-(x-5)=18 | | 18=16x-14x | | 2+4r=30 | | 6(x*2)=216/3 | | 0=3x^2-7x-136 | | 4t^2/5-7t/5-9/10=0 | | 5(7-11)=y-3 | | 3(4x)=72 | | (12-7c)=4(2c-5) | | 0=8t+-5t^2 | | 3y-5=13-y | | -6x+5=2x+77 | | 3x+10=-6x+64 | | -3x-9=5x+47 | | 3x+9y-2=0 | | 3y-2=y-4 |